Image steganography for encryption over network security - Maimon, Elmy Fadly (2017)
The rapidly growth of Internet has increase the data being exchanged through various type of network. Privacy and the safety of data have become concerns as the data being send over the network can be steal and manipulated. Two types of encryption in digital media is cryptography and steganography. Cryptography was commonly used for encryption so that the data cannot be understand by others but this technique was exposed to decryption because anyone would have known that this data contain secret message. Image steganography was created to hide any form of information within digital image without being noticed by others to avoid decryption of the hidden information. Image steganography consist of three elements that is cover image, hidden message and stego image (cover medium + hidden message). The technique studied in this thesis aims to transmit data without losing the quality of cover image and to improve image steganography using MATLAB. To achieve this goal, Least Significant Bit (LSB) algorithm is used for data encoding and decoding. The system was implemented using MATLAB platform. The performance of the image steganography method has been evaluated based on the quality of cover image with stego image, robustness and capacity of data hidden in the stego image. The image steganography for encryption is simple to implement and the selections of image is important to achieve the objective of image steganography. The experimental results prove that the proposed technique conserved the quality of cover image and improve the image steganography by using MATLAB platform.